Does Parenting Style Influence Learning Autonomy? An Empirical Investigation in Higher Education - Dr. Sarah Mufti; Dr. Uzma Rani; Dr. Namra Shahzadi; Tayyaba Shahzadi (Dialogue Social Science Review (DSSR), 2025)
The purpose of this study was to investigate the relationship between undergraduate university students' learning autonomy and the three parenting philosophies. To collect data, the Convenient Sampling technique was employed recruiting 250 university students from 18 to 24 years. The Parental Authority Questionnaires by Buri and the Self-Regulation Questionnaire (Learning), which assessed three parenting philosophies and students' learning autonomy, were used to collect data from the University of Gujrat in Pakistan. The findings showed that parenting methods and learning autonomy did not significantly correlate with gender. Furthermore, measurably significant associations between parenting styles and learning autonomy were found through multiple regression analyses. Furthermore, all parenting styles aside from the mother's authoritativeness and autonomous regulation exhibited a highly significant correlation with controlled regulation. Additionally, there was a strong correlation between parenting styles and controlled regulation. However, when comparing two groups, such as male and female, using the Autonomous and Control variables of the Self-regulation Questionnaire, the results of an independent sample t-test analysis showed that there was no significant correlation between gender differences and learning autonomy. The study's conclusions showed that parental practices had a strong correlation with kids' learning autonomy, albeit these results vary depending on the culture and society. Understanding, decision-making, and flexibility are just a few of the learning components that are included in student achievement. However, a number of mediating factors can have a detrimental impact on academic performance, which can leave students, parents, and teachers unhappy (Brown & Iyengar, 2008, Mufti et al., 2023). Parenting style is one such important component that has a big influence on a child's academic, emotional, and cognitive development. Fewer studies have looked at how parenting styles affect undergraduate students' academic achievement, especially in relation to self-regulation and learning autonomy, despite the fact that a large body of research has examined how parenting styles affect the development of children and adolescents (Meghan, 2011). The purpose of this study is to look into how parenting practices and undergraduate students' learning autonomy relate to one another.